Identifikasi Jenis-Jenis Tumbuhan Yang Memiliki Nilai Konservasi Tinggi (HCVF) Di PT. Gunung Gajah Abadi Kutai Timur - Arbain, Arbain (Jurnal Pertanian Terpadu, 2015)
Identify the types of plants that have high conservation value forest areas naturally At elephant mountain abadi. The method used is by means of exploration is the exploration of an area with a specific purpose, namely to determine the types of plants that have high conservation values ​​are protected for example, government regulations, endemic, medicinal plants and others. Results and discussion on the location of the observations found 297 types. It consists of herbaceous plants, shrubs, trees, lianas and epipit. Very many species of high conservation value based on its status that is protected by government regulation until its status as a fruit-producing plants, medicinal plants, endemic and others. Suggestion; While doing the harvesting is expected to pay attention to the types that are protected by government regulations, especially endangered species and producing fruits. Maintain and cultivate the types of medicinal plants. Save the types of orchids that exist dibatang trees, branches and twigs to a certain area (create a garden of orchids) and maintain the existence of endemic species.